Laparoscopic cholecystectomy with or without drainage in patients with non-complicated benign gallbladder disease: A randomized controlled trial - كنعان, سمير (Latakia University Journal -Medical Sciences Series, 2023)
Background: The routine use of abdominal drainage after laparoscopic cholecystectomy is controversial. The aim of this study was to compare the outcomes of laparoscopic cholecystectomy with or without drainage in patients with non-complicated benign gallbladder disease. Methods: We conducted a randomized controlled trial involving 500 patients who underwent laparoscopic cholecystectomy for symptomatic gallstones. The patients were randomly assigned to receive laparoscopic cholecystectomy with drainage (drain group, n = 300) or without drainage (no-drain group, n = 200). The primary outcome measures were postoperative pain and wound infection. The secondary outcome measures were bile leak, bleeding, and reoperation. Results: The pain scores were significantly higher in the drain group than in the no-drain group at all time points (P < .001). The incidence of wound infection was 6% in the drain group and 3% in the no-drain group (P = .04). The incidence of bile leak was 1% in the drain group and 0% in the no-drain group (P = .25). The incidence of bleeding was 1.7% in the drain group and 0% in the no-drain group (P = .11). The reoperation rate was 0% in both groups. Drainage was associated with longer operative time and hospital stay. Conclusion: In this randomized controlled trial, we found no benefit of routine drainage after laparoscopic cholecystectomy in patients with non-complicated benign gallbladder disease. Drainage was associated with higher pain scores, longer operative time and hospital stay, and higher risk of wound infection. We suggest that routine drainage after laparoscopic cholecystectomy is not necessary and may be harmful for these patients.